Rationality of Antidiabetic in Outpatient with Type 2 Diabetes Mellitus at PKU Muhammadiyah Yogyakarta Hospital, Special Region of Yogyakarta - Indonesia - Urfiyya, Qarriy A.; Aisyah, Aisyah (Universitas Padjadjaran, Indonesia, 2023)
In the past few decades, the number of people with diabetes mellitus has steadily increased in various countries. Type 2 Diabetes Mellitus (DM) is the most common type of DM. An increase follows this significant increase in the number of patients in the use of antidiabetic drugs and the risk of irrational drug use, where drug use evaluation is one of the strategies to reduce it. This study aims to evaluate the rational use of antidiabetics in outpatients with type 2 DM at PKU Muhammadiyah Yogyakarta Hospital, Special Region of Yogyakarta - Indonesia. This study is a retrospective analytical observational study. The data used as reference is patient medical records from October 2021 to March 2022. Antidiabetic accuracy based on Indonesian Endocrinology Society guidelines and Drug Information Handbook ed. 22. A total of 155 medical records patients were included in this study. The result showed that patients with complications (50,4%) were higher than patients without complications (49,6%), with the most complication was nephropathy (67,9%) and the most comorbidity was hypertension (21,2%). The rationality of antidiabetics includes the right patient (94%), the right medicine (74%), the right dosage (100%), the right time administration (100%), and the right interval administration (97%). The rational drug use is expected to reduce the risk of drug side effects, reduce patient treatment costs, and improve patient life quality.